Die hantering van enkele jeugromans van Barrie Hough : 'n leerder-/lesergerigte benadering - Matthee, Freddie Christiaan (Stellenbosch : Stellenbosch University, 2012)
Tesis (M. Ed.) -- Universiteit van Stellenbosch, 1996.